Mosses of Gunung Serapi, Sarawak, Borneo - Mohamed, H.; Yong, K.T.; Bakar, B. (Botanisches Insitut der Universitaet, 2003)
Collections of mosses have been made from the 911 metre high Gunung (Mount) Serapi in Sarawak. A total of 77 species in 37 genera within 17 families were discovered and are enumerated below. Five species are reported for the first time for Borneo: Aerobryidium aureonitens (Hook. ex Schwägr.)Broth., Distichophyllum schmidtii Broth., Mitthyridium fasciculatum subsp obtusifolium (Lindb.) M.Menzel, Papillidiopsis complanata (Dixon) W.R.Buck & B.C.Tan and Trichosteleum stigmosum Mitt. Seventeen species are new records for Sarawak. One family, Bartramiaceae, and 3 genera, Aerobryidium, Leucoloma, Philonotis, are new to Sarawak. The largest family is Calymperaceae, with 6 genera and 21 species, followed by Sematophyllaceae, with 10 genera and 19 species.